Developing Contextual-Based History Learning Media: A Videoscribe Project on the Bongkotan Temple Site for Hindu-Buddhist Heritage Material - Aldi Hendra Pratama (Indonesian Journal of History Education, 2025)
This research addresses the gap in local history education by developing and validating Videoscribe-based learning media focused on the Bongkotan Temple Site, a Hindu-Buddhist heritage site in Wonosobo, Indonesia. Using the ADDIE model within a Research and Development (R&D) framework, the study involved needs analysis, product design, expert validation, and classroom implementation. Data were collected through interviews, questionnaires, and document analysis involving teachers and students at MAN 2 Wonosobo. Validation results from material, media, and practitioner experts showed an average score of 89.04%, indicating very high feasibility. Student responses further affirmed the media’s effectiveness, with an average approval rating of 87%. The findings demonstrate that locally contextualized digital media can enhance historical literacy, engagement, and regional awareness. This study contributes to the discourse on innovative, place-based history pedagogy in post-colonial educational settings.